2015
DOI: 10.1177/0194599815584599
|View full text |Cite
|
Sign up to set email alerts
|

Role of Obesity on the Prognosis of Sudden Sensorineural Hearing Loss in Adults

Abstract: Obesity/overweight would appear to have no significant effect on the prognosis of SSHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Most of these studies on the association between nutrition and HL have reported an increased risk of HL in certain nutritional deficiencies. However, recent studies have also shown that obesity, an excessively increased state of nutrition, increases the risk of HL [84,85,86,87,88,89,90,91,92,93]. A key hypothesis for the mechanism of the relationship between obesity and HL is that deformation of the capillary wall due to excessive fat tissue damaging the delicate inner ear system, resulting in vasoconstriction of the inner ear [94].…”
Section: Evidence That Nutrition Is a Factor Affecting Hlmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies on the association between nutrition and HL have reported an increased risk of HL in certain nutritional deficiencies. However, recent studies have also shown that obesity, an excessively increased state of nutrition, increases the risk of HL [84,85,86,87,88,89,90,91,92,93]. A key hypothesis for the mechanism of the relationship between obesity and HL is that deformation of the capillary wall due to excessive fat tissue damaging the delicate inner ear system, resulting in vasoconstriction of the inner ear [94].…”
Section: Evidence That Nutrition Is a Factor Affecting Hlmentioning
confidence: 99%
“…However, the relationship between obesity and hearing status is reported in contrast to these previous studies. The current literature suggests that obesity is associated with age-related HL and sudden SNHL (SSNHL) [84,85,86,87,88,89,90,91,92]. In addition, underweight and severe obesity have been associated with an increased prevalence of HL in a cross-sectional study in a Korean population [93].…”
Section: Studies On Nutrition and Hearingmentioning
confidence: 99%
“…Aetiology of hearing loss associated with non-otologic surgery and non-cardiopulmonary surgery carried in general anaesthesia is not clear, however there are some pathogenetic mechanism that seems to be involved: changes in middle ear pressure (mechanic and pharmacology), vascular pathology, Cerebrospinal Fluid (CSF) pressure changes, embolism, ototoxic drugs, and other miscellaneous causes. Obesity seems to have no role on the Aetiology and prognosis of SNHL [17].…”
Section: Discussionmentioning
confidence: 97%
“…In the histological study, constricted blood vessels were observed in the stria vascularis part of the cochlea 16 · Moreover, high BMI and dyslipidemia lead to narrowing of arteries and decreased blood flow by causing atherosclerotic vascular disease 17 18 · Adipose tissue affects insulin resistance, energy metabolism, and atherosclerosis through the release of hormones and cytokines, and it may exacerbate inflammation and end-organ damage caused by obesity. Obesity directly leads to worsening of hearing through lipotoxicity and related oxidative stress or indirectly contributes to peripheral hearing degeneration via its comorbidity-related angiopathy and/or neuropathy 19 ·…”
Section: Discussionmentioning
confidence: 99%
“…In the histological study, constricted blood vessels were observed in the stria vascularis part of the cochlea 16 • Moreover, high BMI and dyslipidemia lead to narrowing of arteries and decreased blood flow by causing atherosclerotic vascular disease 17,18 • Adipose tissue affects insulin resistance, energy metabolism, and atherosclerosis through the release of hormones and cytokines, and it may exacerbate inflammation and end-organ damage caused by obesity. Obesity directly leads to worsening of hearing through lipotoxicity and related oxidative stress or indirectly contributes to peripheral hearing degeneration via its comorbidity-related angiopathy and/or neuropathy 19 • Satar et al reported that dyslipidemia could cause cochlear injury by leading to edema in the outer hair cells and the stria vascularis. 20 Lee et al emphasized that elevated total cholesterol and triglyceride (TG) levels, and increased BMI were associated with increased prevalence of SNHL, which occurred as a result of damage due to cochlear ischemia.…”
Section: Discussionmentioning
confidence: 99%